Role of "cell block" in thyroid cytology: A cross sectional study - Rajib, RC; Majid, N; Rahman, MR; Baqui, MN; Shermin, S (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13536 JAFMC Vol.8(1) 2012 pp.30-34